Crucial lncRNAs associated with adipocyte differentiation from human adipose-derived stem cells based on co-expression and ceRNA network analyses - Chen,Kana; Xie,Shujie; Jin,Wujun (PeerJ, 2019)
Background Injection of adipose-derived stem cells (ASCs) is a promising treatment for facial contour deformities. However, its treatment mechanisms remain largely unknown. The study aimed to explain the molecular mechanisms of adipogenic differentiation from ASCs based on the roles of long noncoding RNAs (lncRNAs). Methods Datasets of mRNA–lncRNA (GSE113253) and miRNA (GSE72429) expression profiling were collected from Gene Expression Omnibus database. The differentially expressed genes (DEGs), lncRNAs (DELs) and miRNAs (DEMs) between undifferentiated and adipocyte differentiated human ASCs were identified using the Linear Models for Microarray Data method. DELs related co-expression and competing endogenous RNA (ceRNA) networks were constructed. Protein–protein interaction (PPI) analysis was performed to screen crucial target genes. Results A total of 748 DEGs, 17 DELs and 51 DEMs were identified. A total of 13 DELs and 279 DEGs with Pearson correlation coefficients > 0.9 and p-value < 0.01 were selected to construct the co-expression network. A total of 151 interaction pairs among 112 nodes (10 DEMs; eight DELs; 94 DEGs) were obtained to construct the ceRNA network. By comparing the lncRNAs and mRNAs in two networks, five lncRNAs (SNHG9, LINC02202, UBAC2-AS1, PTCSC3 and myocardial infarction associated transcript (MIAT)) and 32 genes (i.e., such as phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1), protein tyrosine phosphatase receptor type B (PTPRB)) were found to be shared. PPI analysis demonstrated PIK3R1 , forkhead box O1 (FOXO1; a transcription factor) and estrogen receptor 1 (ESR1) were hub genes, which could be regulated by the miRNAs that interacted with the above five lncRNAs, such as LINC02202-miR-136-5p-PIK3R1, LINC02202-miR-381-3p-FOXO1 and MIAT-miR-18a-5p-ESR1. LINC02202 also could directly co-express with PIK3R1. Furthermore, PTPRB was predicted to be modulated by co-expression with LINC01119. Conclusion MIAT, LINC02202 and LINC01119 may be potentially important, new lncRNAs associated with adipogenic differentiation of ASCs. They may be involved in adipogenesis by acting as a ceRNA or co-expressing with their targets.
Keywords: Human adipose tissue-derived stromal stem cells; Adipogenic differentiation; ceRNA; lncRNA; miRNA; Co-expression